Model Event-Based Learning Models In Early Childhood Learning - Andiya, Aflah (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
In the current era of technological and information development, early childhood learning approaches continue to innovate to meet educational needs that are effective and attractive to children. One approach that is increasingly popular is event-based learning or event-based learning. This concept places real events at the center of learning, enabling children to learn through hands-on and contextual experiences. Therefore, it is important to use an appropriate approach in early childhood learning. One approach that has been proven effective and well known in this context is event-based learning. Through these hands-on experiences, children can develop a deeper understanding of abstract concepts such as time, natural cycles or social interactions. Event based learning involves active participation of children in the learning process. They are encouraged to ask questions, try out roles, and come up with their own ideas. The purpose of this research is to seek information or collect data related to event based learning in early childhood learning. The method used in this article is bibliometric analysis using VOSviewer.